Allergic contact dermatitis due to the liquid skin adhesive Dermabond® predominantly occurs after the first exposure. (29th September 2020) - Asai, Chika; Inomata, Naoko; Sato, Megumi; Koh, Nao; Goda, Seiko; Ishikawa, Hideyuki; Tanaka, Masako; Aihara, Michiko
Abstract: Background: The clinical characteristics of patients with allergic contact dermatitis (ACD) due to a skin adhesive containing 2‐octyl cyanoacrylate, Dermabond®, have not yet been elucidated. Objective: To investigate the clinical characteristics of patients with ACD caused by Dermabond® application. Methods: In this retrospective study, 577 patch tested patients were included. We identified patients with positive patch test results for Dermabond® and evaluated their results concerning (meth)acrylates and ethyl cyanoacrylate adhesive. Results: Nine patients had positive patch test results to Dermabond®; six had developed secondary generalization.The mean time between Dermabond® application and ACD onset was 34 days (range, 27‐44) in six patients with ACD after the first use, whereas, in the other three patients, it was 5.6 days (range, 4‐8) after the second use. The time was significantly different between the two groups ( P < .01). Positive reactions to ethyl cyanoacrylate adhesive (Aron Alpha) occurred in seven of nine patients, to ethyl cyanoacrylate 10% pet. in four of eight patients tested, and to 2‐hydroxyethyl methacrylate in one of eight patients tested. Conclusions: Dermabond®‐induced ACD is apparently characterized by a high prevalence of primary sensitization at first exposure to Dermabond®, secondary generalization is frequent, and most patients show cross‐reactivity to ethyl cyanoacrylate.